Benchmarking establishment for green building based on DEA and individual advantage identification. Issue 6 (3rd October 2017) - Wang, Yong-Gang
Abstract: Firstly, methods and evaluation index of the benchmark building of the green building were analyzed. Then establish the benchmark model on the basis of DEA and individual advantage identification in order to help establish the individual benchmarking and group benchmarking for a certain 'Star' Grade. Finally, 15 specific projects in the same area for modeling analysis were selected to determine the benchmarking of such projects in the region.